A prospective cohort study of the presence of SARS-CoV-2 in clinical samples from multiple bodily sites: implications for transmission routes of COVID-19. Issue 1 (5th March 2022) - Liu, Meixian; Huang, Huimin; Bian, Xiqing; Zheng, Zhiyuan; Li, Na; Sun, Baoqing; Wu, Jian-Lin
Abstract: Objective: The coronavirus disease 2019 (COVID-19) epidemic resulting from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has still spread globally. The occurrence of the Delta variant, which is more infectious and spreads faster than earlier forms of the virus that causes COVID-19, makes infection prevention more challenging. Therefore, this study aimed to gain a comprehensive insight into the transmission routes of SARS-CoV-2 for curbing the propagation of SARS-CoV-2 in human populations. Methods: We studied a prospective cohort of 576 patients admitted consecutively to the First Affiliated Hospital of Guangzhou Medical University from January 21 to June 8, 2020. These patients were chosen based on their similar clinical phenotypes or imaging findings. There were 21 (3.6%) laboratory-confirmed COVID-19 patients (16 severe and 5 mild cases) and 555 non-COVID-19 patients. The antibody response and routes and duration of viral shedding were systematically evaluated in serial clinical specimens. Moreover, SARS-CoV-2 RNA was also detected in a mouth rinse, urine, and tear samples. This study was approved by the Medical Ethical Committee of The First Affiliated Hospital of Guangzhou Medical University (approval No. 2020-77). Results: SARS-CoV-2 mainly existed in sputum, nasal and throat swabs, and feces samples. Virus latency was longer in sputum and feces samples than in nasopharyngeal samples. IgG antibody response in respiratory samples was related to disease severity. Although droplets and aerosols are the major transmission routes for COVID-19, covert routes of transmission from asymptomatic patients, contaminated surfaces, and wastewater are also of interest. Conclusion: Our findings provide a solid foundation for developing prophylactic measures against SARS-CoV-2.